Powerful Organic Molecular Oxidants and Reductants Enable Ambipolar Injection in a Large-Gap Organic Homojunction Diode - Smith, Hannah L; Dull, Jordan T.; Mohapatra, Swagat K.; Kurdi, Khaled Al; Barlow, Stephen; Marder, Seth R.; Rand, Barry P.; Kahn, Antoine (ACS Applied Materials and Interfaces, 2022)
Doping has proven to be a critical tool for enhancing the performance of organic semiconductors in devices like organic light-emitting diodes. However, the challenge in working with high ionization- energy (IE) organic semiconductors is to find p-dopants with correspondingly high electron affinity (EA) that will improve the conductivity and charge carrier transport in a film. Here, we use an oxidant that has been recently recognized to be a very strong p-type dopant, hexacyano-1,2,3-trimethylene-cyclopropane (CN6-CP). The EA of CN6-CP has been previously estimated via cyclic voltammetry to be 5.87 eV, almost 300 meV higher than other known high-EA organic molecular oxidants. We measure the frontier orbitals of CN6-CP using ultraviolet and inverse photoemission spectroscopy techniques and confirm a high EA value of 5.88 eV in the condensed phase. The introduction of CN6-CP in a film of large-band-gap, large-IE phenyldi(pyren-1-yl)phosphine oxide (POPy2) leads to a significant shift of the Fermi level toward the highest occupied molecular orbital and a 2 orders of magnitude increase in conductivity. Using CN6-CP and n-dopant (pentamethylcyclopentadienyl)(1,3,5-trimethylbenzene)ruthenium (RuCp*Mes)2, we fabricate a POPy2-based rectifying p−i−n homojunction diode with a 2.9 V built-in potential. Blue light emission is achieved under forward bias. This effect demonstrates the dopant- enabled hole injection from the CN6-CP-doped layer and electron injection from the (RuCp*Mes)2-doped layer in the diode.
Keywords: organic semiconductors; p-dopants; n-dopants; photoemission spectroscopy; p−i−n homojunctions; light emission